Chemical composition of artocarpus odoratissimus, canarium odontophyllum and litsea garciae fruits from Sarawak - Poli, Musfirah (Universiti Malaysia Sarawak (UNIMAS), 2015)
Canarium odontophyllum, Litsea garciae and Artocarpus odoratissimus are among of the indigenous edible fruits that can be found in Sarawak and these highly seasonal fruits are very popular among local people. The fruits collected from different Divisions in Sarawak were analysed for their nutritional properties. The properties analysed include proximate analysis such as moisture content, ash content, crude fat, crude fiber and vitamin C. The results show that both pulps and kernels of C. odontophyllum, L. garciae and A. odoratissimus proved to be important sources of necessary nutrients for human diet. Mineral content in the fruit pulps analysed using atomic absorption spectrophotometer (AAS) shows that potassium (K) is the major element detected in all fruit samples with the highest abundance was detected in the pulps of C. odontophyllum (6116.47–10814.84 mg/kg). The samples are also rich in calcium (Ca), magnesium (Mg) and sodium (Na). Both the fruit pulps and kernels were extracted using Soxhlet extractor and the fatty acids in the oils were esterified prior to gas chromatography-mass spectrometry (GC-MS). The major components occurred in all pulp oils are palmitic acid (C16:0), linoleic acid (C18:2n6c) and oleic acid (C18:1n9c).